Getting used to Conformism: On the Attitudes of Czech Scientists Towards the Totalitarian Regime (in Literary Representations) - Gawarecka, Anna (Porównania, 2024)
The issue of the destruction of the idea of ​​university freedom and the "betrayal of intellectuals", i.e. the complete appropriation and ideologization of academic space by political control mechanisms, is still the subject of interest of historians, ethicists and publicists. For the history of Czech science, the personal motives of scientists who were forced to revoke their beliefs seem to be less important, as more importance should be attached to the enormity of the devastation caused in the sphere of research development caused by reducing the methodological and theoretical space to one theory and method - in a simplified way derived from Marxist philosophy. Such motives gain the weight in the literary representations of the scientific community. In the reality of regime repression, in which violence covered all areas of life and did not bypass any social group, the scientific community was located on the margin of the mainstream of topics discussed by dissident and exile writers, but it appeared in their texts, especially, although not exclusively, in the works of authors with professional experience in academic work, who play an often complicated game with both elements of autobiography and the conventions of roman à clef.